Editorial: Role of probiotics and probiotics' metabolites in food and intestine - Fusco, Vincenzina; Wu, Rina; Zhang, Wenyi; Zhai, Qixiao (Frontiers in Microbiology, 2023)
The emergence and exploration of new disciplines and technologies have provided new ideas and opportunities for probiotic science and industry development. The interaction between diet and intestinal flora has become a new target for human health regulation. Recently, probiotic supplements have received increasing attention as an important tool to modulate the gut microbiota (Brito Sampaio, Fusco, de Brito Alves, Leite de Souza, 2022). Lactic acid bacteria (LAB) are powerful probiotics in the intestinal tract that can participate in metabolic regulation by directly or indirectly influencing the inhibition or activation of the signaling pathways. LAB can synthesize a variety of active metabolites, producing short-chain fatty acids, vitamins, enzymes, organic acids and antibacterial peptides. These metabolites can regulate the intestinal epithelium's barrier function and provide health benefits to the host. Studies have found that probiotics have a variety of biological activities (Leite de Souza, de Brito Alves, Fusco, 2022; Brito Sampaio et al., 2022). However, their application is still limited due to the poor colonization and the unclear mechanism of the induction of metabolites in the host involved in the interaction between pathogens and bacterial communities, etc. Therefore, this Research Topic aimed to collect new studies focused on probiotics and probiotics' metabolites in food and intestine with combined phenotyping, genotyping and targeting strategies as well as the multi-omics technologies.